Clinical and Cerebrospinal Fluid Abnormalities as Diagnostic Tools of Tuberculous Meningitis - Lestari, Fiona; Dian, Sofiati; Parwati, Ida (Althea Medical Journal, 2016)
Background: Tuberculous meningitis (TBM) is the most severe form of extrapulmonary tuberculous (TB) disease and remains difficult to diagnose. The aim of the study was to determine the diagnostic value of clinical and laboratory findings of cerebrospinal fluid (CSF) examinations for diagnosing TBM using bacterial culture result as the gold standard.Methods: A prospective cross sectional study was carried out to 121 medical records of hospitalized TBM patients in neurological ward at Dr. Hasan Sadikin General Hospital Bandung, from 1 January 2009â31 May 2013. The inclusion criteria were medical records consisted of clinical manisfestations and laboratory findings. The clinical manisfestations were headache and nuchal rigidity, whereas the laboratory findings were CSF chemical analysis (protein, glucose, and cells) and CSF microbiological culture. Validity such as sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) for clinical and laboratory findings were calculated, using bacterial culture result as the gold standard.Results: The most clinical findings of TBM was nuchal rigidity and it had the highest sensitivity value, but the lowest spesificity value. Decreased of CSF glucose had the highest sensitivity value compared to other laboratory findings, but the value was low.Conclusions: The clinical manisfestations and the laboratory findings are not sensitive and specific enough for diagnosing TBM. [AMJ.2016;3(1):132â6]Â DOI:Â 10.15850/amj.v3n1.725